2015
DOI: 10.1158/1078-0432.ccr-14-0450
|View full text |Cite
|
Sign up to set email alerts
|

MET Amplification Status in Therapy-Naïve Adeno- and Squamous Cell Carcinomas of the Lung

Abstract: Purpose: MET is a potential therapeutic target in lung cancer and both MET tyrosine kinase inhibitors and monoclonal antibodies have entered clinical trials. MET signaling can be activated by various mechanisms, including gene amplification. In this study, we aimed to investigate MET amplification status in adenoand squamous cell carcinomas of the lung. We propose clearly defined amplification scores and provide epidemiologic data on MET amplification in lung cancer.Experimental Design: We evaluated the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
140
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(160 citation statements)
references
References 37 publications
14
140
0
6
Order By: Relevance
“…These data support the hypothesis of a primary mechanism of resistance, such as EGFR p.T790M mutation and MET gene copy number alteration, in tumour specimens of patients with no prior exposure to EGFR TKI [15]. In our series, the prevalence of MET FISH positive cases at baseline (14%) was in line with Cappuzzo et al [11] (11.1%), but higher than values reported by others [16] (see below).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data support the hypothesis of a primary mechanism of resistance, such as EGFR p.T790M mutation and MET gene copy number alteration, in tumour specimens of patients with no prior exposure to EGFR TKI [15]. In our series, the prevalence of MET FISH positive cases at baseline (14%) was in line with Cappuzzo et al [11] (11.1%), but higher than values reported by others [16] (see below).…”
Section: Discussionsupporting
confidence: 92%
“…Cappuzzo et al [11], investigated a series of radically resected NSCLC and reported a MET amplification in approximately 11.1% of the cases. In other studies, the positive rate was much lower (3%), but the definition of MET highly amplified tumours was limited to those exceeding the mean of 6 gene copy number per cell [16,23]. However, in one of these studies, the Authors also found an additional 30% of cases with MET intermediate or low altered signals; both squamous and non-squamous treatment-naive NSCLC showed different extents of MET copy number gains of the intermediate or low type, according to the interpretation criteria used [16], supporting the concept of a complex array of MET changes.…”
Section: Discussionmentioning
confidence: 87%
“…Recent data suggest that HGF/MET protein expression alone may be an oversimplification of the oncogenic driver status of "METpositive" NSCLC, where mutations or translocations and amplification reduce the requirement for ligand activation and lead to sustained or altered signaling properties of the receptor. Although IHC data have been shown to correlate with MET amplification (66), clinical study biomarker data (summarized in Table 4) have not confirmed any clear-cut relationships between MET mutation, amplification, and overexpression, when collectively applied as predictive biomarkers for MET-targeted therapy. IHC-based MET expression has not been a successful biomarker approach in clinical studies of monoclonal antibodies, and current clinical and biomarker data suggest that genetic changes in MET, in particular gene amplification, may be the preferred biomarkers for MET TKI therapy (21,(63)(64)(65).…”
Section: Discussion: Potential Of Met As a Biomarker In Lung Cancermentioning
confidence: 99%
“…One possible drawback of using the MET/CEP7 gene ratio is that this technique may not identify all amplified patients due to the unique pathophysiology of NSCLC. In some cases, amplicons occur that include the centromere control protein and the MET gene or the centromere protein but not the MET gene; in the latter case, the ratio may be falsely lowered (66).…”
Section: Met Amplificationmentioning
confidence: 99%
“…20,21). Indeed, it is estimated that 5% to 20% of NSCLC patients who develop resistance to EGFR inhibitors have MET amplification as a mechanism of resistance (22)(23)(24). In addition, MET amplification has also been observed in 20% of metastatic colorectal (6,20) and up to 20% of gastric cancer patients (16,25).…”
mentioning
confidence: 99%